Amphibian and reptile dataset across different land-use types in Guinea-Bissau, West Africa - Francisco dos Reis-Silva; Fernanda Alves-Martins; Javier Martínez-Arribas; Cristian Pizzigalli; Sambu Seck; Ana Rainho; Ricardo Rocha; Ana Filipa Palmeirim (Biodiversity Data Journal)
West Africa is exceptionally biodiverse, yet its wildlife remains largely understudied despite the rapid and ongoing land-use changes. Large swaths of Guinea-Bissau’s landscape were historically characterised by native forest-savannah mosaics. However, key areas of savannah habitats have been converted to rice agroecosystems and forests are being transformed into cashew monocultures at unprecedented rates. Amphibians and reptiles comprise some of the most threatened species by human-induced habitat change and yet are not as studied as other vertebrate terrestrial taxa. Here, we provide two comprehensive datasets on amphibians and reptiles (classes Testudines and Squamata) from northern Guinea-Bissau: (1) a standardised survey dataset (encompassing sampling events and occurrences) in forest fragments, cashew orchards and rice paddies and (2) an opportunistic dataset reporting occurrences across the entire study area. Standardised surveys were carried across 21 sampling sites, seven in each habitat type, while opportunistic surveys include all other records. For standardised surveys, a total of 703 amphibian and 265 reptile (class Squamata) encounters are reported, corresponding to nine and 13 taxa, respectively. Opportunistically, we report 62 amphibian and 93 reptile encounters, corresponding to 10 amphibian taxa, 25 Squamata taxa and two turtles (class Testudines).Based on 126 sampling hours of both diurnal and nocturnal standardised surveys, in addition to opportunistic surveys, these datasets comprise the first overview for amphibians and reptiles in mainland Guinea-Bissau across two seasons and different habitat types. Each of the 968 standardised and 155 opportunistic occurrences corresponds to a genus or species and is accompanied by geographic coordinates, a timestamp and, for standardised data, the land-use type. The datasets fill the distribution gaps in Guinea-Bissau of at least three species, including the frog Hildebrandtia ornata, the skink Trachylepis keroanensis and the snake Dendroaspis polylepis – and include the re-discovery of the lizard Latastia ornata in Guinea-Bissau. Before this work, the L. ornata was only known from the 1938 holotype in Bafatá (ca. 60 km away from the study area) and, in 2023, from Guinea-Conakry (ca. 700 km away from the type specimen location).